The Role of Spiritual Auditors to Prevent Fraud in Regional Government Institutions - Siregar, Helly Aroza (Journal of Applied Accounting, 2025)
The purpose of this study is to analyze whether government internal auditors with spiritual intelligence can play a role in preventing fraud in government. This study took government internal auditors assigned to the Financial and Development Supervisory Agency (BPKP) in province level as the subject. The data analysis method used was the Structural Equation Model (SEM) with the AMOS application. The results of the study proved that spiritual intelligence has a positive and significant influence on auditor performance, auditor performance and spiritual intelligence have a positive and significant impact on fraud prevention, and auditor performance can provide a mediating effect in the influence of spiritual intelligence on fraud prevention. Keywords: Spiritual Intelligence; Auditor Performance; Fraud Prevention